The clinical observation on the treatment of multiple plantar warts with plum-blossom needling combined with tazarotene cream and imiquimod cream - LI Fengchun; XU Jiaoxiong; HE Renliang; LI Hui; YAN Lijuan; MA Yunan (Pifu-xingbing zhenliaoxue zazhi)
Objective To observe the efficacy of plum-blossom needling combined with tazarotene cream and imiquimod cream in the treatment of multiple plantar warts. Methods Sixty patients with multiple plantar warts were randomly divided into the observation group, control groups 1 and 2, 20 cases per group. After removal part of warts and thickened stratum corneum with scalpel, the observation group was treated with plum-blossom needling in combination with tazarotene cream and imiquimod cream. And the control group 1 was treated with fractional CO2 laser in combination with tazarotene cream and imiquimod cream, while the control group 2 was treated with tazarotene cream and imiquimod cream alone. Plum-blossom needling and fractional CO2 laser were given once every 10 days for a total of no more than 9 times. All patients were treated for 3 months and adverse reactions were observed during the follow-up period. The clinical efficacy was compared among three groups. The recurrence rates were observed during a 3-month follow-up after the treatment. Results The cure rates in observation group, and control groups 1 and 2 were 94.44%, 88.24% and 45.0%, respectively (χ2=14.63, P<0.05). However, there were no significant differences in cure rate, total number of treatment and the duration of treatment between the observation and control group 1 (cure rate: Z=-0.61, P>0.0167, total number of the treatment: Z=-0.37, P>0.0167, the duration of the treatment: Z=-0.36, P>0.0167). In contrast, the observation group had higher cure rate (Z=-3.23, P<0.0167), fewer treatments (Z=-2.57, P<0.0167) and shorter treatment duration (Z=-2.59, P<0.0167) in comparison to the control group 2. The recurrence rates were comparable among the three groups. No severe adverse reactions were observed in any groups during the treatment. Conclusions Plum-blossom needling combined with tazarotene cream and imiquimod cream displays a comparable efficacy to fractional CO2 laser in combination with tazarotene cream and imiquimod cream, but superior to tazarotene cream and imiquimod cream alone, for multiple plantar warts. Plum-blossom needling combined with tazarotene cream and imiquimod cream is a simple and effective regimen for multiple plantar warts.